Yesus Kristus Lahir 25 Desember: Studi Historis - Tolop Marbun (STT Pelita Dunia, 2023)
Abstract: This research aims to discover historical evidence of Christmas celebrations before 274AD to disprove the claim that December 25th is paganism. Christmas on December 25th is accused of being a pagan celebration. The accusation of paganism at Christmas mainly refers to a Christian theologian named Paul Ernst Jablonski asserted in the 18th century that Christmas is a pagan celebration. Jablonski's claim refers to the Emperor of Constantinople's foundation of Christmas in 316 and Emperor Aurelia's nomination of December 25th as Dies Natalis Solis Invicti in 274M. The historical technique with heuristic steps was applied in the investigation. Heuristic is a Greek word that means